2012
DOI: 10.1080/03075079.2011.648373
|View full text |Cite
|
Sign up to set email alerts
|

Making sense of higher education: students as consumers and the value of the university experience

Abstract: Abstract/Summary:In the global university sector competitive funding models are progressively becoming the norm, and institutions/courses are frequently now subject to the same kind of consumerist pressures typical of a highly marketised environment. In the United Kingdom, for example, students are increasingly demonstrating customer-like behaviour and are now demanding even more 'value' from institutions. Value, though, is a slippery concept and has proven problematic both in terms of its conceptualisation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
188
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 263 publications
(212 citation statements)
references
References 91 publications
4
188
0
3
Order By: Relevance
“…At its most basic (e.g., Gale 1994;Oh 1999;Ostrom and Iacobucci 1995), this branch of the literature considers just attributes and price, the consequence expressed as Bvalue for money.^Other trade-off perspectives however (Grönroos 1997;Heskett et al 1997) identify that Bgive^components go beyond price, and incorporate both acquisition costs (time, effort, maintenance) and psychological costs (e.g., fear and anxiety). As a result, some later contributions (e.g., Mayr and Zins 2012;Ruiz, Gremler, Washburn and Carrión 2008;Woodall, Hiller and Resnick 2014) have adopted a wider perspective on the benefits/ sacrifices relationship than that which focuses purely on value for money. These look to compile a more complex/granular account that incorporates elements of the means-end approach.…”
Section: The Case For Trade-offsmentioning
confidence: 99%
“…At its most basic (e.g., Gale 1994;Oh 1999;Ostrom and Iacobucci 1995), this branch of the literature considers just attributes and price, the consequence expressed as Bvalue for money.^Other trade-off perspectives however (Grönroos 1997;Heskett et al 1997) identify that Bgive^components go beyond price, and incorporate both acquisition costs (time, effort, maintenance) and psychological costs (e.g., fear and anxiety). As a result, some later contributions (e.g., Mayr and Zins 2012;Ruiz, Gremler, Washburn and Carrión 2008;Woodall, Hiller and Resnick 2014) have adopted a wider perspective on the benefits/ sacrifices relationship than that which focuses purely on value for money. These look to compile a more complex/granular account that incorporates elements of the means-end approach.…”
Section: The Case For Trade-offsmentioning
confidence: 99%
“…In this context, Woodall et al (2014) highlight a number of outcomes from a university education subsumed within practical, social, strategic and personal categories. The physical document is the most tangible outcome and, therefore, the most product like, whereas other outcomes, which may be signified by possession of the degree, including knowledge/learning, transferable skills and business understanding, have greater degrees of intangibility.…”
Section: Consumerisation In Higher Educationmentioning
confidence: 99%
“…Recently, research has shown there has been an increase in evidence suggesting that consumer-based practices, notions and perceptions are permeating into UK higher education institutions (HEIs) (Nixon et al 2016;Woodall et al 2014). Many of these developments have occurred since the introduction of tuition fees, following which UK HEI leaders have implemented strategies, policies and procedures which focus on income and revenue maximisation (Natale and Doran 2012), as opposed to the traditional staple learning and teaching experiences (Marginson 2012;Nixon et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, academics report as much less positive about their WLB than other groups such as administrative staff and widespread, rapid changes in HE over the past 30 years are believed to be the main cause (Hunt 2006). Since 1982, UK HE institutions have been increasingly subject to consumerist pressures typical of a highly marketised environment with students increasingly demonstrating customer-like behaviour and demanding more value from institutions (Woodall, Hiller, and Resnick 2014). A plethora of government initiatives have had a substantial impact on the context and content of academic work (Hunt 2006).…”
Section: Wlb In Academiamentioning
confidence: 99%